Kearifan Lokal dalam Pelestarian Lingkungan (The Lokal Wisdom in Environmental Sustainable) - Husni Thamrin (Lembaga penelitian dan pengabdian kepada masyrakat, 2013)
Environmental issues from day to day more complex and the environmental crisis. One of the causes of the crisis is the perception and behavior of humans who pursue economic interests and pragmatic life style. Currently there is a shift in the way people think of the importance of virtue or wisdom to the values of the all materialism, pragmatic and capitalism. In Indonesian society, especially Riau terms with the values of local wisdom in governance and environmental conservation. This can be seen in the expression of proverb indigenous, teaching point, hymes, poems, myth etc. maintain Behavior of environmental wisdom can also be seen in the socio-cultural system and the use of technology. But it is unfortunate local knowledge, especially in environmental conservation has been almost eroded from the community caused by pragmatic interests. The consequences of this erosion of local knowledge makes environmental degradation and a very dangerous crisis survival of mankind on this earth. Therefore it is very overlooked revitalize indigenous values , as a fundamental step to meet the challenges of the environmental crisis, change thinking and behavior to preserve human and environmental sustainability for the safety and harmony of mankind on earth.